A research in Turkish words of Discourse of Shams Tabrizi - اسماعیل تاج‌بخش (تاریخ ادبیات)
In this article, twenty Turkish words used in the text of Discourse of Shams have been introduced and etymologically identified, and it is a small step in the jurisprudence and linguistics (fiqh al-lughah) section of comparative literature. It is also a sign and proof of the influence of Turkish language and literature on Persian language and literature. It is believed to be useful for those who study mystical works.